Glutathione Depletion by L-Buthionine-S,R-Sulfoximine Induces Apoptosis of Cardiomyocytes through Activation of PKC-δ - Kim, Young-Ae (The Korean Society of Applied Pharmacology, 2013)
In the present study, we investigated the effect of intracellular glutathione (GSH) depletion in heart-derived H9c2 cells and its mechanism. L-buthionine-S,R-sulfoximine (BSO) induced the depletion of cellular GSH, and BSO-induced reactive oxygen species (ROS) production was inhibited by glutathione monoethyl ester (GME). Additionally, GME inhibited BSO-induced caspase-3 activation, annexin V-positive cells, and annexin V-negative/propidium iodide (PI)-positive cells. Treatment with rottlerin completely blocked BSO-induced cell death and ROS generation. BSO-induced GSH depletion caused a translocation of PKC-δ from the cytosol to the membrane fraction, which was inhibited by treatment with GME. From these results, it is suggested that BSO-induced depletion of cellular GSH causes an activation of PKC-δ and, subsequently, generation of ROS, thereby inducing H9c2 cell death.